What is Addiction? - Collins Peter; Ross Don; Spurrett David (Kincaid Harold The MIT Press, 2010)
This book demonstrates a sweeping advance over the simplistic conception embedded in popular culture. Introduction: What is Addiction?, Neuroeconomics of Addiction: The Contribution of Executive Dysfunction, Neurobiology of Pathological Gambling, Genetic Influences on Addiction: Alcoholism as an Exemplar, Addiction as a Breakdown in the Machinery of Decision Making, Economic Models of Pathological Gambling, Addiction: A Latent Property of the Dynamics of Choice, Addiction and Altruism, The Core Process in Addictions and Other Impulses: Hyperbolic Discounting Versus Conditioning and Cognitive Framing, Measuring Dispositions to Bundle Choices, Neural Recruitment During Self-Control of Smoking: A Pilot fMRI Study, Anticipatory Processing as a Transdisciplinary Bridge in Addiction, Impulsivity and Its Association with Treatment Development for Pathological Gambling and Substance Use Disorders, Medical Models of Addiction, Addiction and the Diagnostic Criteria for Pathological Gambling, Irrational Action and Addiction, Defining Addiction and Identifying the Public Interest in Democracies.